CUTANEOUS LEISHMANIASIS: AN EXPERIENCE AT UMDC - Tabinda Roheen; Tanzeela Rasheed; Shazia Aslam et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: Leishmaniasis is caused by single-cell parasites of the genus Leishmania. More than 10 different Leishmania species can cause human diseases. The two main clinical manifestations of leishmaniasis are:  Visceral leishmaniasis  Cutaneous leishmaniasis This report is presented to highlight the incidence of cutaneous leishmaniasis in non-endemic areas like Faisalabad.